OP0229 Both High Titer of RF/ACPA at Baseline Is Closely Linked with High Level of Baseline Plasma TNF Level Which Resulted in Low Drug Level and Low Clinical Response in Infliximab Treatment in RA Patients: Post-Hoc Analysis of A Double-Blind Clinical Study (Rising Study). (15th July 2016) - Takeuchi, T.; Miyasaka, N.; Inui, T.; Yano, T.; Yoshinari, T.; Abe, T.; Koike, T.
Abstract : Background: Baseline RF or ACPA positivity is reported to be linked with clinical response of some non-TNF bDMARDs in RA. However, its impact on the efficacy of TNF inhibitors was controversy. Objectives: To evaluate the influence of baseline RF and ACPA "titers" on the patients characteristics and efficacy of infliximab (IFX) in RA patients using data of the RISING study, a randomized double-blind clinical study in MTX-refractory RA (ref-1, NCT00691028 ). Methods: In the RISING study, after patients received 3 mg/kg IFX infusion at Weeks 0, 2, and 6, they were randomly assigned to infusion of 3, 6, or 10 mg/kg IFX, every 8 weeks from Week 14 to Week 46 in a double-blind manner (n=307, all patients received 3 mg/kg treatment until Week 14). Serum IFX levels and clinical responses based on DAS28-CRP were evaluated at Weeks 14 and 54. Results: Both baseline RF and ACPA titers showed significant positive correlation with baseline plasma TNF level. We hypothesized that "both RF-High and ACPA-High" was correlated with higher TNF level. Then, we stratified the patients into 3 classes using baseline RF/ACPA titers; "Low/Low" (RF: <55 U/ml, ACPA: <42 U/ml), "High/High" (RF: ≥160 U/ml, ACPA: ≥100 U/ml), and "Middle" (did not meet above criteria for either class), and compared baseline patient characteristics, serum IFX level, and DAS28-CRP among these 3 classes. Among above 3 classes, significant difference was observed in plasma baseline TNF level, which was previously reported to be closely correlated with low serum IFX level, and low clinical response (ref-2); low TNF level in Low/Low class, high TNF level in High/High class, and intermediate value in Middle class (median: 0.73, 1.15, and 0.91 pg/ml, respectively, p<0.0001). In addition, high serum IFX level and low DAS28-CRP in Low/Low class, low serum IFX level and high DAS28-CRP in High/High class, and intermediate values in Middle class were observed at Week 14. In Low/Low, Middle, High/High classes, median IFX levels at Week 14 were 1.5, 0.7, and 0.4 μg/ml, respectively (p=0.0004), and median DAS28-CRP at Week 14 were 3.17, 3.53, and 3.82, respectively (p=0.0256). Similar tendency was observed at Week 54 in patients who continued 3 mg/kg treatment, but not in those who received dose-escalation from 3 to 6 or 10 mg/kg after Week 14. Conclusions: High titers of both RF/ACPA at baseline is correlated with high baseline plasma TNF level which might be resulted in low IFX level and low clinical response in patients with continuing 3 mg/kg treatment, but not in patients receiving 6 or 10 mg/kg treatment. Baseline RF/ACPA might be the index of dose-escalation of IFX in RA. References: Takeuchi T, et al. Mod Rheumatol 2009;19:478. ref-2: Takeuchi T, et al. Ann Rheum Dis 2011;70:1208. Disclosure of Interest: T. Takeuchi Grant/research support from: AbbVie GK, Asahi Kasei Pharma, Astellas Pharma, AYUMI Pharmaceutical, Bristol-Myers KK, Chugai Pharmaceutical, Daiichi Sankyo, Eisai, Taisho Toyama Pharmaceutical, Takeda Pharmaceutical, Teijin Pharma, Consultant for: AbbVie GK, Asahi Kasei Medical, Astellas Pharma, AstraZeneca KK, Bristol-Myers KK, Daiichi Sankyo, Eli Lilly Japan, Janssen Pharmaceutical KK, Merck Serono, Mitsubishi Tanabe Pharma, Nippon Kayaku, Novartis Pharma KK, Takeda Pharmaceutical, Speakers bureau: AbbVie GK, Astellas Pharma, Bristol-Myers KK, Celtrion, Chugai Pharmaceutical, Daiichi Sankyo, Eisai, Janssen Pharmaceutical KK, Mitsubishi Tanabe Pharma, Nippon Kayaku, Pfizer Japan, Takeda Pharmaceutical, N. Miyasaka: None declared, T. Inui Employee of: Mitsubishi Tanabe Pharma, T. Yano Employee of: Mitsubishi Tanabe Pharma, T. Yoshinari Employee of: Mitsubishi Tanabe Pharma, T. Abe: None declared, T. Koike Consultant for: Eli Lilly Japan, Pfizer Japan, Speakers bureau: AbbVie GK, Astellas Pharma, Bristol-Myers KK, Chugai Pharmaceutical, Daiichi Sankyo, Eisai, Mitsubishi Tanabe Pharma, Pfizer Japan, Santen Pharmaceutical, Teijin Pharma, UCB Japan